2020
DOI: 10.1155/2020/9016583
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Resistivity Anisotropy of Loaded Coal Samples

Abstract: In this paper, an experimental study of the variation of resistivity of coal samples in different bedding directions at 1 MHz frequency was performed by establishing an experimental system for resistivity testing of coal under triaxial stress. The low-pressure nitrogen gas adsorption (LP-N2GA) experiment and scanning electron microscopy (SEM) were obtained to analyze the pore-fracture structural characteristics of coal samples and the influence on resistivity anisotropy. Furthermore, the fundamental cause of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Lyu et al believed that the adsorption capacity of gas and electrical conductivity presented a power function relationship [10]. Li et al analyzed the pore-fracture structure characteristics of coal samples and their influence on resistivity anisotropy [11]. Therefore, in order to better study the microscopic damage activities in the process of nitrogen fracturing coal, the American Agilent U1733C LCR tester was used to study the evolution characteristics of the resistivity of the loaded coal during nitrogen injection.…”
Section: Introductionmentioning
confidence: 99%
“…Lyu et al believed that the adsorption capacity of gas and electrical conductivity presented a power function relationship [10]. Li et al analyzed the pore-fracture structure characteristics of coal samples and their influence on resistivity anisotropy [11]. Therefore, in order to better study the microscopic damage activities in the process of nitrogen fracturing coal, the American Agilent U1733C LCR tester was used to study the evolution characteristics of the resistivity of the loaded coal during nitrogen injection.…”
Section: Introductionmentioning
confidence: 99%
“…Li [35] tested the resistivity change of coal with different loading modes and found that the resistivity curve showed a "V"-shaped change during the loading process. Li [36] also studied the anisotropy of resistivity in a loaded coal sample. These experiments showed that the electrical resistivity test can reflect the dynamic changes in the internal structure in tectonic coal mechanical experiments.…”
Section: Introductionmentioning
confidence: 99%